Visual grammar and the principles of design on children’s interactive ebook (Palíndromo, 2014)
The picturebook, also presented in digital media allows growth of interactive features, dynamic elements and sound stimuli. This article, however, presents a descriptive-analytical study that specifi- cally addresses the visual structure of child ebook Treasure Kai and the Lost Gold Shark Island. The visual syntax of the product is considered, describing the basic arrange- ment of visual elements in the principles of design as a communication strategy in multimedia interface. Such questions de- fine the visual organization of the publica- tion, which must be legible and consistent with the general meaning of the message. Based on this study, we identified strategies used to define the visual graph structure of child ebook. Among them, there is the for- mal, color and textures used to differenti- ate interactive objects, specific treatments backgrounds characteristics to indicate the changes in history and contrasts that contribute to rank the elements in the pro- cess of reading in the digital environment.
Keywords: picturebook; children´s book app; visual grammar